Antecedents of training effectiveness in Bahrain - Yaqoot, Ehsan Saeed Idrees; Wan Mohd Noor, Wan Shakizah; Mohd Isa, Mohd Faizal (Sprint Investify, 2017)
This study focuses on antecedents of the training programmes’ effectiveness at public sector organizations in Bahrain. A Kirkpatrick model is utilized as a partial research framework and tested as the dependent variable training effectiveness in this study.This study further examines the relationship between the independent variables, trainer and social support toward training effectiveness. The survey instrument was developed for data collection and the questionnaires were distributed to the staff working in the public sector in Bahrain. The total usable questionnaires are 128. The study adopts a quantitative approach using SPSS statistic approach. The outcomes also discover that both antecedents have a positive and a significant relationship with the training effectiveness at various Kirkpatrick’s levels.